Developing inclusive education policy and practice for looked after children - Joe Francis (Scottish Journal of Residential Child Care)
Inclusive education is not a reality for all and it is vital that those charged with providing a quality education to children who have different abilities or face a range of challenges know what is likely to prove effective in helping all pupils within the education system to succeed to the best of their ability (Sebba and Sachdev, 1997). Given all the evidence that looked-after children have extraordinary educational needs (Dixon and Stein, 2002; 2005; Francis, 2000; 2007; Goddard, 2000; HM Inspectors of Schools and the Social Work Services Inspectorate, 2001; Jackson and Sachdev, 2001) and the belief in some quarters that looked-after children in general require special education measures, it is important to consider whether a broader interpretation of the current statutory requirements relating to inclusive education for children with 'additional support needs' might enhance the education of this vulnerable group.